2021
DOI: 10.1111/jace.18027
|View full text |Cite
|
Sign up to set email alerts
|

Electric field‐assisted solid‐state reaction of BaCO3‐TiO2 system

Abstract: We report phase transition process during the solid-state reaction of BaCO 3 -TiO 2 system under the assistance of electric field. Experiments were conducted at a constant heating rate with preset field strength and current limit. Solid-state reaction was completed upon reactive flash sintering taking place at ~1002℃ under 200 V/cm. Hexagonal BaTiO 3 phase, which rarely occurs at such temperatures, was obtained after flash sintering at a current density of 23.5 mA/mm 2 . It is speculated that oxygen deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The electrochemical reactions that happened when using DC mode were also observed in Na 3 Zr 2 (SiO 4 ) 2 (PO 4 ) 44 with the formation of a secondary phase, Na 2 ZrSi 2 O 7 , and accumulation of NaO x at the cathode. DC reducing effects were also observed in air in the literature when creating defect fluorite phases of Gd 2 Zr 2 O 7 , 32 and also by triggering cubic to hexagonal phase transitions in BaTiO 3 33 …”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The electrochemical reactions that happened when using DC mode were also observed in Na 3 Zr 2 (SiO 4 ) 2 (PO 4 ) 44 with the formation of a secondary phase, Na 2 ZrSi 2 O 7 , and accumulation of NaO x at the cathode. DC reducing effects were also observed in air in the literature when creating defect fluorite phases of Gd 2 Zr 2 O 7 , 32 and also by triggering cubic to hexagonal phase transitions in BaTiO 3 33 …”
Section: Discussionmentioning
confidence: 54%
“…DC reducing effects were also observed in 32 and also by triggering cubic to hexagonal phase transitions in BaTiO 3 . 33 Intensity of the reactions was dictated by the maximum current density achieved during RFS. Tests under the same condition (onset at 1200 • C und 250 V⋅cm −1 , AC mode, in air) at different current densities indicated that a certain current density intensity is necessary to promote full reac-tion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 52 ] This effect would apply even in the absence of the flash event. As a matter of fact, during RFS of CCTO [ 46 ] (starting with an amorphous powder) and BTO [ 56 ] crystallization/reactions took place during Stage I, i.e., prior to the flash event, when Joule heating is small. Furthermore, in these instances, there is no contribution from the rapid rise in temperature (thermal runaway) to accelerate the synthesis rate.…”
Section: Mechanisms Of Reactive Flash Sinteringmentioning
confidence: 99%